TETRACYCLINE ADSORPTION FOR PRAWN FARM WASTEWATER USING ZINC OXIDE NANOPARTICLES BIOSYNTHESIZED IN ASPERGILLUS ARENARIOIDES EAN603 SUPERNATANT - MOHD NOOR, NUR NABILAH (2024)
In recent years, many antibiotics found in environment, especially in wastewater. Tetracycline (TC) which consider one of broad-spectrum antibiotics has been widely use in Malaysia’s aquaculture, causing water pollution and health issues. A zinc oxide (ZnO) nanoparticle catalyst was produced to investigate its characteristics, optimization and mechanism for TC adsorption in prawn farm wastewater. Biosynthesis of ZnO NPs via a simple method using fungus extract from Aspergillus arenarioides EAN603. The structural, morphological and optical properties of the synthesized ZnO NPs- A. arenarioides EAN603 are analyzed using several techniques such as ultraviolet-visible spectroscopy (UV-Vis), field emission scanning electron microscopy (FE-SEM), fourier transform infrared spectroscopy (FTIR), X-Ray diffraction analysis (XRD), Raman spectroscopy and atomic force microscopy (AFM). The results showed that ZnO NPs have suitable properties for adsorption with confirmation of absorption band in UV-Vis, and nanoparticles shape of size distribution of 43.7 to 88.7 nm of FESEM. FTIR result observed a strong peak at 1422 cm-1 and 773 cm-1 for Raman spectra peak which is the most prominent peak for ZnO NPs. AFM morphology reveals a crystal shape with a bumpy surface. The effects of various parameters, including ZnO NP dosage (1.0g/L-2.0g/L), TC concentration (0.5g/L-2.0g/L), pH (4-6), and reaction time (60 mins – 70 mins), are systematically investigated to optimize the adsorption. Optimum conditions for maximum TC adsorption efficiency were determined as 93% for 1.5 g/L of ZnO NPs dosage, 0.5 mg/L of TC concentration, 65 mins for reaction time and pH at 5. The adsorption mechanism of TC was analyzed by using isotherm and kinetics study which showed that this study fits the Freundlich model for adsorption isotherm and pseudo-second-order for the kinetic model. Overall, this study demonstrates that ZnO NPs- A. arenarioides EAN603 hold great promise for the efficient removal of TC from prawn farm wastewater through adsorption process